2020
DOI: 10.1029/2019wr026447
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Stoichiometric Reservoir Sedimentation Regulates Methane Accumulation in China's Three Gorges Reservoir

Abstract: The river-reservoir continuum drives a separation of sedimentation along the longitudinal hydrodynamic gradients, potentially causing imbalanced stoichiometric sedimentation. However, there are still uncertainties regarding the contribution of imbalanced stoichiometric sedimentation to methane emissions along this continuum. A 2-year field survey and in situ experiments were conducted in China's Three Gorges Reservoir (TGR), a river-valley-dammed reservoir. Sediments were trapped and collected to analyze for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Greater TP concentrations will result in high‐chlorophyll a , low‐O 2 , eutrophic conditions (DelSontro et al., 2018), with higher rates of methanogenesis in sediments (West et al., 2016). The negative correlation between CH 4 and C:P (Figure 6e) shows that more C relative to P leads to lower CH 4 , and has been reported in reservoirs (Z. Li et al., 2020). This finding agrees with a growing body of work arguing that nutrient stoichiometry, and not just absolute concentration, is important in controlling aquatic biogeochemistry (Graeber et al., 2021; Peacock et al., 2022; Stutter et al., 2018; Taylor & Townsend, 2010), including GHG emissions (Peacock et al., 2017; Webb et al., 2021).…”
Section: Resultssupporting
confidence: 74%
“…Greater TP concentrations will result in high‐chlorophyll a , low‐O 2 , eutrophic conditions (DelSontro et al., 2018), with higher rates of methanogenesis in sediments (West et al., 2016). The negative correlation between CH 4 and C:P (Figure 6e) shows that more C relative to P leads to lower CH 4 , and has been reported in reservoirs (Z. Li et al., 2020). This finding agrees with a growing body of work arguing that nutrient stoichiometry, and not just absolute concentration, is important in controlling aquatic biogeochemistry (Graeber et al., 2021; Peacock et al., 2022; Stutter et al., 2018; Taylor & Townsend, 2010), including GHG emissions (Peacock et al., 2017; Webb et al., 2021).…”
Section: Resultssupporting
confidence: 74%
“…In addition, the pre-impoundment clearance also reduced decomposition of organic carbon and inhibited the significant increase in CH 4 emissions in the TGR. During reservoir flushing, degassing would occur because of rapid depressurization and strong aeration, resulting in increased emissions of dissolved CH 4 and lowering of CH 4 concentration downstream [ 6 , 41 ]. Overall, the TGD regulated the CH 4 emission regime of the Yangtze, causing dissolved CH 4 to increase in the upper reach and decrease in the lower reach.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of POC in a river can be significantly influenced by dams. At first, damming increased losses of river connectivity and reduced water flow in the main channel, which possibly decreased the transport of POC after damming due to the long HRT, further resulting in bulk accumulation and burial of POC in reservoirs (Ulseth and Hall Jr, 2015;Li et al, 2017a;Almeida et al, 2019;Li et al, 2020a;Wang et al, 2020).…”
Section: Cascade Damming Effect On Input and Accumulation Of Pocmentioning
confidence: 99%
“…The largest share of CH4 emissions may be due to OC retention and mineralization in the reservoir (Shi et al, 2017). Recent research showed that imbalanced stoichiometric sedimentation mediated CH4 accumulation in the mid-part of China's Three Gorges Reservoir (Li et al, 2020a). However, the findings supported that reservoir operation strategy significantly impacts the patterns of CH4 accumulation.…”
Section: Introductionmentioning
confidence: 97%